Validation of a CFD model for wave energy system dynamics in extreme waves. (15th January 2023) - Katsidoniotaki, Eirini; Shahroozi, Zahra; Eskilsson, Claes; Palm, Johannes; Engström, Jens; Göteman, Malin
Abstract: The design of wave energy converters should rely on numerical models that are able to estimate accurately the dynamics and loads in extreme wave conditions. A high-fidelity CFD model of a 1:30 scale point-absorber is developed and validated on experimental data. This work constitutes beyond the state-of-the-art validation study as the system is subjected to 50-year return period waves. Additionally, a new methodology that addresses the well-known challenge in CFD codes of mesh deformation is successfully applied and validated. The CFD model is evaluated in different conditions: wave-only, free decay, and wave–structure interaction. The results show that the extreme waves and the experimental setup of the wave energy converter are simulated within an accuracy of 2%. The developed high-fidelity model is able to capture the motion of the system and the force in the mooring line under extreme waves with satisfactory accuracy. The deviation between the numerical and corresponding experimental RAOs is lower than 7% for waves with smaller steepness. In higher waves, the deviation increases up to 10% due to the inevitable wave reflections and complex dynamics. The pitch motion presents a larger deviation, however, the pitch is of secondary importance for a point-absorber wave energy converter. Highlights: A high-fidelity model of a point-absorber wave energy converter in extreme waves is successfully developed and validated on experimental data. A novel morphing mesh method that facilitates the extreme wave–structure interaction modeling in OpenFOAM is implemented and validated. Waves with a 50-year return period are numerically reproduced within an accuracy of 2%. Low deviation is found between the numerical and corresponding experimental values for the RAOs and mooring force. The developed numerical model can supplement to a large extent the costly experimental campaigns.